1996
DOI: 10.1128/jb.178.9.2539-2550.1996
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the regulatory region of a cell interaction-dependent gene in Myxococcus xanthus

Abstract: ⍀4403 is the site of a Tn5 lac insertion in the Myxococcus xanthus genome that fuses lacZ expression to a developmentally regulated promoter. Cell-cell interactions that occur during development, including C-signaling, are required for expression of Tn5 lac ⍀4403. We have cloned DNA upstream of the ⍀4403 insertion site, localized the promoter, and identified a potential open reading frame. From the deduced amino acid sequence, the gene disrupted by Tn5 lac ⍀4403 appears to encode a serine protease that is disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 68 publications
2
84
1
Order By: Relevance
“…The generation time of the groEL1-complemented double-deletion mutant YL0308 was 6.92 Ϯ 0.29 h and that of the groEL2-complemented mutant YL0310 was 7.05 Ϯ 0.23 h in CTT medium, respectively. Several studies have re- ported reduced expression of genes at the Mx8 attB site (6,19,33). The quantitative-PCR results indicated that the levels of expression of the transposed groEL1 and groEL2 genes were approximately 30% to 50% and 75% to 90%, respectively, of that in the wild-type strain DK1622 at 24 h and 28 h in CTT cultures.…”
Section: Vol 192 2010 Functions Of Groel Genes In Myxococcus Xanthumentioning
confidence: 95%
“…The generation time of the groEL1-complemented double-deletion mutant YL0308 was 6.92 Ϯ 0.29 h and that of the groEL2-complemented mutant YL0310 was 7.05 Ϯ 0.23 h in CTT medium, respectively. Several studies have re- ported reduced expression of genes at the Mx8 attB site (6,19,33). The quantitative-PCR results indicated that the levels of expression of the transposed groEL1 and groEL2 genes were approximately 30% to 50% and 75% to 90%, respectively, of that in the wild-type strain DK1622 at 24 h and 28 h in CTT cultures.…”
Section: Vol 192 2010 Functions Of Groel Genes In Myxococcus Xanthumentioning
confidence: 95%
“…Fragments carrying putative σ 54 promoters and enhancer elements were generated using PCR and purified using the Promega Wizard SV Gel and PCR Clean-Up System as described by the manufacturer. Purified promoter fragments were cloned into the promoterless lacZ vector pREG1727 (53), which is used to create lacZ transcriptional fusions, and transformed into M. xanthus WT strain DK1622. The in vivo activity of the promoter fragments in developing cells was determined by measuring β-galactosidase-specific activities at various times after starvation was induced as previously described (54).…”
Section: Site-directed Mutagenesis Of Putative σ 54 Promoters and β-Gmentioning
confidence: 99%
“…Based on previous experience in our laboratory (1,6,7,12,32), the majority of transformants have a single copy of the plasmid integrated at attB. To eliminate colonies with unusual developmental lacZ expression, we screened at least 10 transformants on TPM agar plates containing 40 g of 5-bromo-4-chloro-3-indolyl-␤-D-galactopyranoside per ml.…”
Section: Construction Of M Xanthus Strains and Determination Of Laczmentioning
confidence: 99%
“…Genes that depend on C signaling for expression are activated at different times after 6 h into development, and some show partial expression in a csgA mutant, whereas others show no expression (23,29). Expression of all such genes examined thus far could be rescued by codeveloping the csgA mutant with wild-type cells (to supply C signal) (1,6,7,23,32) or by adding a 17-kDa fragment of CsgA (22). A higher level of the CsgA fragment was needed to rescue expression of a gene normally induced at the onset of sporulation than for a gene induced earlier, indicating different thresholds for response (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation